STUDY OF PERIPHRASES RELATED TO GEORTONYM (Scientific journal of the Fergana State University, 2024)
Linguistic features of periphrases related to holiday names are studied in the article. The review of the scientific works carried out on periphrasis in world and Uzbek linguistics is covered. Periphrases describe, exaggerate, explain and fill in important features of things, events, which are not revealed by their names, serve to effectively express the name. In Uzbek linguistics, there are many periphrasis related to religious geortonyms. These pictorial expressions are a special form of national thinking and acquire linguistic and cultural importance in the practical manifestation of the nation's worldview, knowledge and concepts, and religious beliefs. The periphrasis used to exaggerate the cultural characteristics of various geortonyms are analyzed with the necessary examples and explanations.